Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

For the quadratic equation [tex]\(-3x^2 + 4x + 1 = 0\)[/tex], enter the correct values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex], and then set up the quadratic formula.

[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]

[tex]\( a = \)[/tex] [tex]\(\square\)[/tex]

[tex]\( b = \)[/tex] [tex]\(\square\)[/tex]

[tex]\( c = \)[/tex] [tex]\(\square\)[/tex]

[tex]\[ x = \frac{-\square \pm \sqrt{\square^2 - 4(\square)(\square)}}{2(\square)} \][/tex]


Sagot :

Alright, let's proceed step-by-step to fill in the values for the given quadratic equation [tex]\(-3x^2 + 4x + 1 = 0\)[/tex].

1. Identifying coefficients:

For the quadratic equation of the form [tex]\(ax^2 + bx + c = 0\)[/tex]:
- [tex]\(a = -3\)[/tex]
- [tex]\(b = 4\)[/tex]
- [tex]\(c = 1\)[/tex]

2. Substituting coefficients into the quadratic formula:

The quadratic formula is given by:

[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]

Substituting the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] into the formula:

[tex]\[ x = \frac{-4 \pm \sqrt{4^2 - 4(-3)(1)}}{2(-3)} \][/tex]

So, the values we should enter are:

[tex]\( a = -3 \)[/tex]

[tex]\( b = 4 \)[/tex]

[tex]\( c = 1 \)[/tex]

Thus, the quadratic formula becomes:

[tex]\[ x = \frac{-4 \pm \sqrt{4^2 - 4(-3)(1)}}{2(-3)} \][/tex]